Being the Change. 12 ways foundations are transforming themselves to t ransform their impact - Ridgway, Abigail; Bockstette, Valerie; Seneviratne, Andria; Cain, Miya; Foster, Tracy (FSG, 2018)
Many foundations are adopting new approaches for creating social chang e—approaches that aim to influence the actions and investments of the public and private sector, as well as address the complex conditions t hat hold social problems in place.Based on interviews with 114 practit ioners representing 50 foundations and 8 philanthropic services organi zations, Being the Change explores how foundations are applying their assets, knowledge, skills, networks, and people in new ways in order t o create impact at scale and change systems.